2022
DOI: 10.3390/jof8030252
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Mode of Antifungal Action of Heat-Stable Antifungal Factor (HSAF) in Neurospora crassa

Abstract: Heat-stable antifungal factor (HSAF) isolated from Lysobacter enzymogenes has shown a broad-spectrum of antifungal activities. However, little is known about its mode of action. In this study, we used the model filamentous fungus Neurospora crassa to investigate the antifungal mechanism of HSAF. We first used HSAF to treat the N. crassa strain at different time points. Spore germination, growth phenotype and differential gene expression analysis were conducted by utilizing global transcriptional profiling comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The production of chitinase and glucanase, which break down chitin and glucan, respectively, by L. capsici CK09 contribute to its biocontrol activity against the fungal phytopathogen [ 70 , 71 , 72 ]. HSAF, a broad-spectrum antifungal activity produced by L. capsici CK09, can interfere in ceramide synthesis and polarized hyphal growth [ 73 ], inhibit conidia germination [ 74 ] and trigger autophagy-mediated degradation [ 75 ]. Thus, the production of HSAF, together with chitinases and β-1,3-glucanases, exert the contact-independent antifungal activity of L. capsici CK09.…”
Section: Discussionmentioning
confidence: 99%
“…The production of chitinase and glucanase, which break down chitin and glucan, respectively, by L. capsici CK09 contribute to its biocontrol activity against the fungal phytopathogen [ 70 , 71 , 72 ]. HSAF, a broad-spectrum antifungal activity produced by L. capsici CK09, can interfere in ceramide synthesis and polarized hyphal growth [ 73 ], inhibit conidia germination [ 74 ] and trigger autophagy-mediated degradation [ 75 ]. Thus, the production of HSAF, together with chitinases and β-1,3-glucanases, exert the contact-independent antifungal activity of L. capsici CK09.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal proteins have a crucial role in the antagonistic effect of B. subtilis. These proteins can inhibit mycotoxin production, disrupt cell walls, deform the mycelium, cause abnormal spore germination, and inhibit the growth and reproduction of fungi (Rismondo and Schulz, 2021;Liu et al, 2022). A study investigating of the mechanism of inhibition of Colletotrichum gloeosporioides by antifungal proteins revealed that the mycelium structure after antifungal protein treatment was damaged, the cell wall was ruptured, the cytoplasmic structure was disturbed, and the contents of the cell flowed out (Liu et al, 2020;Oliveira Silva et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, HSAF was extracted from the metabolites of OH11 and further purified by high-performance liquid chromatography (HPLC). , In brief, HSAF was extracted from an OH11 fermentation broth by ethyl acetate, separated and purified by HPLC, and then, HSAF powder was obtained by freeze-drying. Finally, the HSAF powder (purity >95%) was dissolved in dimethyl sulfoxide (DMSO) to obtain a stock solution (4 g/L), and it was stored at 4 °C …”
Section: Methodsmentioning
confidence: 99%
“…Many microorganisms and their secondary metabolites are used as biological control agents to protect host plants and prevent disease development . Heat-stable antifungal factor (HSAF) (Figure C) belongs to the family of polycyclic tetramate macrolactams (PTMs), and it exhibits strong and extensive inhibitory effects on fungi and oomycetes. HSAF is primarily produced by the Gram-negative bacteria Lysobacter enzymogenes C3 and OH11, which are used for agricultural biological control. L. enzymogenes OH11 was first isolated from the rhizosphere soil of green pepper in the Jiangsu Academy of Agricultural Sciences of China by our laboratory .…”
Section: Introductionmentioning
confidence: 99%